2022
DOI: 10.3389/fphys.2021.744968
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone Suppression by Progestin-Primed Ovarian Stimulation Is Associated With Higher Implantation Rate for Patients With Polycystic Ovary Syndrome Who Underwent in vitro Fertilization/Intracytoplasmic Sperm Injection Cycles: Comparing With Short Protocol

Abstract: BackgroundMany studies have demonstrated the positive clinical value of progestin-primed ovarian stimulation (PPOS) in patients with polycystic ovary syndrome (PCOS) who underwent assisted reproductive technology. However, the underlying factors contributing to this phenomenon remain unclear. We conducted a retrospective observational study to compare the clinical outcomes of women with PCOS who underwent PPOS or the short protocol to identify possible factors that influence the outcome.MethodsThis study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In the present study, the mean LH level of the letrozole combined with the PPOS regimen seemed more stable and appropriate than that in the PPOS protocol alone. Nevertheless, contrary studies demonstrated that LH suppression by PPOS was associated with a higher implantation rate for patients with PCOS than with a short protocol (Chen et al, 2021). Hence, the optimal LH level required for the PPOS protocol in PCOS patients is worth exploring.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the mean LH level of the letrozole combined with the PPOS regimen seemed more stable and appropriate than that in the PPOS protocol alone. Nevertheless, contrary studies demonstrated that LH suppression by PPOS was associated with a higher implantation rate for patients with PCOS than with a short protocol (Chen et al, 2021). Hence, the optimal LH level required for the PPOS protocol in PCOS patients is worth exploring.…”
Section: Discussionmentioning
confidence: 99%
“…We included three RCTs ( 15 , 16 , 33 ) and six retrospective cohort studies ( 11 , 17 , 29 32 ) involving 2289 women. Most included studies were conducted in China ( 11 , 15 , 17 , 30 33 ), and the others were in Japan ( 29 ) and Iran ( 16 ). The average age of women was 28-34 years old.…”
Section: Resultsmentioning
confidence: 99%
“…The average age of women was 28-34 years old. Four studies ( 15 , 17 , 31 , 32 ) applied medroxyprogesterone acetate (MPA) as the oral progestin in the PPOS group; two used GnRH-a short protocol in the control group, and the other two used GnRH antagonist protocol. Three studies ( 16 , 29 , 30 ) used dydrogesterone in the PPOS group, with GnRH antagonist protocol in all control groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported varying LH levels on the hCG trigger day in different patient groups using the MPA protocol. In women with PCOS, LH levels ranged from 1.62 to 2.52 IU/L ( 40 43 ), while in infertile women with normal ovarian reserve, LH levels were between 1.56 and 3.54 IU/L ( 12 , 14 , 44 46 ). Poor responders showed LH levels in the range of 2.4 to 5.55 IU/L ( 6 , 47 49 ).…”
Section: Discussionmentioning
confidence: 99%